2017
DOI: 10.1177/0306624x16687046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Group-Focused Cognitive-Behavioral Coaching Program on Depressive Symptoms in a Sample of Inmates in a Nigerian Prison

Abstract: This study investigated the effects that a group-focused cognitive-behavioral coaching program had on depressive symptoms of a sample of inmates from Nsukka Prisons, Enugu State, Nigeria. The design of the study was pretest-posttest control group . The participants were 30 male inmates, experiencing high levels of depressive symptoms, and randomly assigned to treatment and control groups. The primary outcome measure was depression symptoms as measured using Beck's Depression Inventory. Repeated-measures ANOVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Hope-based therapy protocol defines hope as a cognitive means in which a person can obtain his/her goal [22]. For a long period of time, this therapy was used to overcome mental illness [23]. The conventional understanding was that hope-based therapy is linked to a pathological replacement of psychotherapy and is believed to be a means of overcoming mental illness.…”
Section: Positive Psychological Strengths As Mediating Variablementioning
confidence: 99%
“…Hope-based therapy protocol defines hope as a cognitive means in which a person can obtain his/her goal [22]. For a long period of time, this therapy was used to overcome mental illness [23]. The conventional understanding was that hope-based therapy is linked to a pathological replacement of psychotherapy and is believed to be a means of overcoming mental illness.…”
Section: Positive Psychological Strengths As Mediating Variablementioning
confidence: 99%
“…Given the mhGAP-IG’s emphasis on psychotherapy for mood disorders and the prison’s difficulties in providing psycho-pharmaceuticals, it could also consider training staff to provide manualized psychotherapy. A small controlled study in Enugu State, for example, has shown that a group-focused cognitive-behavioural coaching programme can reduce depression symptoms among inmates [ 39 ]. However, this is an under-researched area, and more studies are needed to determine which therapies are most cost-effective to deliver in LMIC correctional facility populations.…”
Section: Recommendationsmentioning
confidence: 99%
“…Given the mhGAP-IG's emphasis on psychotherapy for mood disorders and the prison's di culties in providing psycho-pharmaceuticals, it could also consider training staff to provide manualized psychotherapy. A small controlled study in Enugu State, for example, has shown that a group-focused cognitive-behavioural coaching programme can reduce depression symptoms among inmates [40]. However, this is an under-researched area, and more studies are needed to determine which therapies are most cost-effective to deliver in LMIC correctional facility populations.…”
Section: Recommendationsmentioning
confidence: 99%